Decreased Rac1 Cardiac Expression in Nitrofen-Induced Diaphragmatic Hernia - Nakamura, Hiroki; Zimmer, Julia; Puri, Prem (European Journal of Pediatric Surgery, 2018)
Aim The high incidence of cardiac malformations in humans and animal models with congenital diaphragmatic hernia (CDH) is well known. The hypoplasia of left heart is common among fetuses with CDH and has been identified as a poor prognostic factor. However, the precise mechanisms underlying cardiac maldevelopment in CDH are not fully understood. Ras-related C3 botulinum toxin substrate 1 (Rac1) plays a key role in cardiomyocyte polarity and embryonic heart development. Deficiency of Rac1 is reported to impair elongation and cytoskeletal organization of cardiomyocytes, resulting in congenital cardiac defects. We designed this study to test the hypothesis that Rac1 expression is downregulated in the developing hearts of rats with nitrofen-induced CDH.Materials and Methods Following ethical approval (REC1103), time-pregnant Sprague Dawley rats received nitrofen or vehicle on gestational day 9 (D9). Fetuses were sacrificed on D18 and D21 and divided into CDH and control (CTRL) (n = 6 for each group and time point). Quantitative real-time polymerase chain reaction (qRT-PCR), Western blotting, and confocal–immunofluorescence microscopy were performed to detect cardiac gene and protein expression of Rac1.Main Results qRT-PCR and Western blot analysis revealed that Rac1 expression was significantly decreased in the CDH group compared with controls (p < 0.05). Confocal–immunofluorescence microscopy revealed that Rac1 cardiac expression was markedly decreased in the CDH group compared with controls.Conclusion Decreased cardiac Rac1 expression in the nitrofen-induced CDH suggests that Rac1 deficiency during morphogenesis may impair structural cardiac remodeling, resulting in congenital cardiac defects.
Keywords: congenital diaphragmatic hernia; Rac1